Integrating a learning management system with a student assignments digital repository: a case study - Díaz, Francisco Javier (2015)
The integration of different platforms in the academic environment is a challenge within the field of information technology. In the field of e-learning, where learning management systems are used for courses development, their integration with other platforms and applications is interesting, in particular with digital repositories. This article describes the integration of Moodle with the DSpace repository. The integration process consists of two stages, in order to establish full communication to and from the repository. For communication from Moodle to the repository, with the goal of consulting and transferring elements from DSpace, modules already implemented were used. The current stage is implementing a specific module in order to establish communication in the other direction and allow transferring resources from the LMS to the repository. This module is very useful for educational material that can be made publicly available through a repository and thus transcending the borders of an educational environment.